Deviant behaviors in library use: a case study of three universities in Nigeria (2014)
Research on library deviance in Nigeria has largely relied on librarians’ accounts, which often portray students as “deviants” and libraries as “victims”. However, a holistic account should incorporate narratives from both students and librarians in the analysis of deviant behaviors in library utilization. Some common trends of deviance and the implication on library utility in selected universities were discovered through observations and interviews. The study reveals a gap in the security of students’ personal belongings, inadequate electricity supply, and a wide range of deviant behaviors associated with the use of information and communication technologies (ICT) in the library. The impact of these lapses thus put much pressure on both librarians and student users. The study recommends proper funding of libraries to enable the adoption of a 21st Century Library Model, which guarantees a variety of spatial and safety arrangements in curbing the menace of deviants in library utilization.